Comparative study on rice-fish and Taro (Panikachu)-fish culture under integrated farming system in Bangladesh (University Journal of Zoology, Rajshahi University, 2007)
Key words: Rice-fish culturel taro-fish culture, farming system Univ. j. zool. Rajshahi Univ. Vol.23, 2004. pp. 17-21